Pediatric acute hospitalization for anorexia nervosa: an economic evaluation - Maria Rosaria Marchili; Elena Bozzola; Stefano Guolo; Silvio Marchesani; Giulia Spina; Cristina Mascolo; Stefano Vicari; Isabella Tarissi De Jacobis; Massimiliano Raponi; Alberto Villani (BMC, 2024)
Abstract Background Anorexia nervosa (AN) is a psychiatric disorders which may potentially led to a high risk of health medical complications, suicide and self-harming behaviour. Since Covid-19 pandemic onset in March 2020, evidence suggested an increase occurrence of AN. The main aim of the retrospective analysis is to define the cost of hospitalization in the acute phase (HAP) at IRCCS Bambino Gesù Children Hospital, Rome, Italy, over 2 years study. Secondary purposes are defining the main risk factors for a prolonged hospitalization (including age, sex and comorbidities) and the possible influence of Covid-19 pandemic on AN admission and hospital stay. Methods for the purpose of the study, we included children and adolescents aged less than 18 years, admitted to IRCCS Bambino Gesù Children Hospital, Rome, Italy, with a diagnosis of AN. Medical costs were calculated consulting the Lazio Regional Health Service Tariffs. Basing on the date of hospital admission, patients were later divided into two subgroups: subgroup A included patients hospitalized prior than Covid-19 onset (from March 2019 to February 2020) and subgroup B those admitted after (from March 2020 to October 2022). Results a total of 260 patients has been included in the study with a median age of 15 years (range 6-18 years). The total health care cost of AN hospitalized patients was of EUR 3,352,333 with a median cost of EUR 11,124 for each admission (range EUR 930 − 45,739) and a median daily cost of EUR 593 (range EUR 557-930). Median cost was higher in case of comorbidities, guarded patients, enteral feeding. A prolonged hospitalization has been documented in subgroup A with a higher economic burden. Conclusions the economic burden of eating disorders is of note. Adequate sanitary policies as well as health economic analyses are required to gain insight into the cost-effectiveness of AN management. Trial registration 2526-OPBG-2021.